Suprapatellar nail – the gold standard in the treatment of tibia fractures - Casola, Leando; Iglesias, Matias; Matías-Joannas, Germán; Eslava, Santiago; Martínez, María José; Gaillard, Juan Manuel; Arrondo , Guillermo Martin (Journal of the Foot & Ankle, 2023)
Objective: Demonstrate the experience of the team of leg and foot surgeons in tibia instrumentation by the suprapatellar approach for all tibia fractures that meet the indication of an endomedullary nail over three years. Methods: Forty patients were operated on, and after applying inclusion and exclusion criteria, 14 were excluded, totaling 26 patients. The Olerud & Molander (0–100) and Lower Extremity Functional Scale (LEFS) (80/80, 100%) scores were used. Knee pain was evaluated by subdividing the knee into six quadrants to assess the anatomical location of the discomfort. Results: The mean Olerud & Molander was 76.92, and the mean LEFS was 72.33. Five patients presented pain in the knee quadrant 3, reproducing this at maximum knee flexion, and one in quadrant 5, the site of the proximal locking nail, which resolved with its removal. None presented pain at the site of nail entry or femoropatellar pain. Conclusion: Suprapatellar nail instrumentation for tibia fractures has become the gold standard in treating these fractures in the Cirujanos Especialistas en Piena e Pie due to its technical advantages and favorable postoperative evolution. Level of Evidence IV; Therapeutic Studies; Case Series.